Inching towards a new horizon - Mallick, Dwijen; Ayub Ali, Md.; Halder, Joseph; NGO Forum for Drinking Water Supply and Sanitation (Bangladesh) (Dhaka : NGO Forum for Drinking Water Supply & Sanitation, 1999)
With reference to Bangladesh.
Includes bibliographical references (p. 112).
Keywords: Water-supply -- Bangladesh; Sanitation -- Bangladesh; Rural poor -- Health and hygiene -- Bangladesh